ON SOLUTIONS OF THE DISCRETE-TIME ALGEBRAIC RICCATI EQUATION - Soleha, Soleha (MATEMATIKA, 2010)
. On solving the optimal control for the linear discrete-time system based on quadratic performance indexes will be obtained the hermitian solutions of discrete-time algebraic Riccati equation. The existence of that solution can be identified by an invariant subspace which has certain properties. In this paper we investigate some properties of discrete-time algebraic Riccati equation related to an invariant subspace as steps to identify them.